BULLOUS PEMPHIGOID A RARE AUTOIMMUNE DISEASE: A CASE REPORT - Biradar, S. M.; Dhanavidya, S.; Kavya, P.; Keerthi, T.; Sunanda, N.; Marapur, S. C.; Warad, Vijaykumar; Kalyane, N. V. (International Journal of Medicine and Medical Research, 2019)
Background. Bullous pemphigoid (BP) is a rare autoimmune blistering skin disease in the elderly and it is manifested by cutaneous blisters on the skin lesions. The objective was to emphasize the rare case of BP. Methods. A case report of BP in a 58-year-old male patient admitted to a dermatology ward is presented. Results. A 58-year-old male patient with complaints of fluid-filled skin lesions, was examined initially over the trunk, gradually progressed involving B/L upper and lower extremities. Even though the patient was treated with the recommended therapy of corticosteroid (Dexamethasone) along with adjuvant drugs, new skin lesions continued to develop, and the patient’s condition worsened. The Prednisolone was started in place of Dexamethasone on the fifth day of treatment at its higher dose (50mg/day), the Prednisolone proved its efficacy to combat the extensive condition of BP. Conclusions. Bullous pemphigoid is a distressing blistering skin disease. Untreated disease is often fatal because of the susceptibility to infection and fluid-electrolyte disturbances. The mortality of patients with bullous pemphigoid has been significantly reduced with the advent of new therapies and treatment modalities. The treatment with systemic and topical corticosteroids forms the mainstay of treatment along with other adjuvant drugs. In the present case study, the use of Prednisolone has proven its efficacy in the extensive disease state of BP and improved the patient’s quality of life.